2014
DOI: 10.1089/tmj.2014.0008
|View full text |Cite
|
Sign up to set email alerts
|

CardioGuard: A Brassiere-Based Reliable ECG Monitoring Sensor System for Supporting Daily Smartphone Healthcare Applications

Abstract: We propose CardioGuard, a brassiere-based reliable electrocardiogram (ECG) monitoring sensor system, for supporting daily smartphone healthcare applications. It is designed to satisfy two key requirements for user-unobtrusive daily ECG monitoring: reliability of ECG sensing and usability of the sensor. The system is validated through extensive evaluations. The evaluation results showed that the CardioGuard sensor reliably measure the ECG during 12 representative daily activities including diverse movement leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Several reports have been published, in which wearable devices achieved very positive results with high diagnostic accuracy [3][4][5][6]. It was demonstrated that a garment-inserted electrocardiography (ECG) system can obtain similar results to those achieved with the conventional treadmill system during exercise testing,which may also include obtaining echocardiographic images [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports have been published, in which wearable devices achieved very positive results with high diagnostic accuracy [3][4][5][6]. It was demonstrated that a garment-inserted electrocardiography (ECG) system can obtain similar results to those achieved with the conventional treadmill system during exercise testing,which may also include obtaining echocardiographic images [3].…”
Section: Introductionmentioning
confidence: 99%
“…Asimilar system (consisting of accelerometer and ECG) was also used to monitor heart rate and activities of rescuers (fire fighters and Civil Protection rescuers) during emergency interventions [4]. Kwon et al [5] investigated a brassiere-based ECG monitoring system (Cardio-Guard), which showed a high degree of reliability for daily continuous ECG monitoring in women. What is important, all wearable ECG systems presented to be comfortable during tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of a heart rate sensing brassiere was reported in 2014 34 , and efforts have been made to utilize technology-sensing bras to detect breast cancer 35,36 . However, to our knowledge there have been no published investigations that have assessed the validity or reliability of heart rate sensing bras during exercise.…”
mentioning
confidence: 99%
“…Prior studies have addressed such obtrusiveness. A popular approach is to reduce the user’s attention and consciousness by embedding the sensors into accessories, such as a wristband and a belt [ 2 , 3 , 6 , 7 ]. However, in this approach, monitoring is only possible when users are wearing such sensor-embedded accessories, limiting the use cases to clinical or fitness scenarios.…”
Section: Introductionmentioning
confidence: 99%